The impact of maritime activities on the environment in Malaysia - Abang Fauzi, Abang Fadzli; Ismail, Mohd Azril (2012)
Malaysia's seas are among the most biologically diverse in the world, with a variety of ecosystems and natural resources important to the livelihood and sustenance of the people.The environment is related to the maritime activities include shipping, oil and gas industry, tourism, mariculture and others.These maritime activities have been effect the environment in Malaysia such as pollution in marine environment, and degradation of air quality.As a maritime nation, Malaysia is a party to a number of international conventions dealing with pollutions that caused by maritime activities, which laid down important rules to be followed by state parties to prevent and control the impact of maritime activities in the environment in Malaysia.